National Workshop to Integrate Climate Knowledge Products in ATVET Curriculum: Farm Mechanization, Cooperative Organization, Marketing, And Rural Land Administration Programs - Belay, Berhanu; Ambaw, Gebermedihin; Makonnen, Brook T.; Bulo, Million; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Climate change education, particularly through curriculum development and the capacity-building of instructors teaching climate-related subjects, is critical in supporting climate change mitigation and adaptation in agriculture. A workshop was organized to integrate climate knowledge products (CKP) into the Agricultural Technical and Vocational Education and Training (ATVET) curriculum in this context. Before the curriculum development, participants received training on climate basics and climate-smart agriculture, which provided a strong foundation for informed curriculum design. The curriculum development initiative was directed toward ATVET colleges, based on the premise that their graduates are expected to work at the grassroots level, where communities are highly vulnerable to the impacts of climate change. A collaborative initiative between the Ministry of Labor and Skills (MoLS) and the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) influenced ATVET policy to incorporate a course entitled 'Applying Weather and Climate Information to Manage Agricultural Production Risk,' which was included across all agricultural disciplines in three successive rounds of curriculum development efforts. The workshop participants included the trainer (ATVET colleges) and the employer (Ministry of Agriculture). In the third round, held from March 10 to 15, 2025, technical staff from ATVET colleges, AICCRA, the Ministry of Agriculture (MoA), MoLS, the Ethiopian Institute of Agricultural Research (EIAR), and the Ethiopian Meteorological Institute (EMI) collaboratively developed a stand-alone course. This course will serve six programs: Agricultural Mechanization – Farm Machinery Operation, Agricultural Mechanization – Farm Machinery Mechanics, Rural Land Administration, Agricultural Cooperative Accounting and Auditing, Agricultural Cooperative Business Management, and Agricultural Cooperative Marketing. A total of 22 professionals participated in the workshop. The course content includes customized modules on climate basics, climate risk analysis, climate risk management, and reporting climate change effects, tailored to each program's specific needs. The Teaching, Training, and Learning Materials (TTLM) for five of the six programs were finalized, edited, and officially distributed to ATVET colleges for implementation. Moving forward, a tailored training program for staff teaching climate-related courses and a follow-up on implementing the new curriculum have been identified as the next priority steps.